Auxiliary data from SIMBA-type sea ice mass balance buoy 2020T81 - Lei, Ruibo; Cheng, Bin; Hoppmann, Mario; Nicolaus, Marcel; Regnery, Julia (In: Lei, R et al. (2023): Temperature and heating induced temperature difference measurements from SIMBA-type sea ice mass balance buoy 2020T81, deployed during MOSAiC 2020/21 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.958413, 2023)
Geographic position, barometric pressure, tilt and compass.
Keywords: Arctic Ocean; mass balance; MOSAiC-ICE; Sea ice; SIMBA; Temperature